Development of Android-Based Digital Teaching Materials Using Articulate Storyline 3 to Increase Student Motivation and Learning Outcomes in Natural and Social Science Subjects - Aprilia Rizqi Sri Sofiantari; Tri Astuti (Postgraduate, University of Mataram, 2024)
Natural and Social Sciences (IPAS) is one of the main subjects at the elementary school level, where to achieve maximum results in learning IPAS, it requires active student involvement during learning activities. However, the low understanding of teachers about current technology makes it difficult for students to understand the subject matter due to the limited use of learning media. Therefore, researchers want to develop an android-based digital teaching material that can be used by students wherever they are and can be used repeatedly. Researchers used the Research and Development (RnD) research type using the ADDIE model. This study aims to produce android-based digital teaching materials assisted by articulate storyline 3 on the subject matter of IPAS material oh environment so damaged for Class V Elementary School with valid, practical and effective qualifications. The validation results of android-based digital teaching materials obtained a material validation percentage of 95% with very feasible qualifications, 75% media validation with feasible qualifications, and obtained practitioner validation of 100% with very feasible qualifications. The practicality of android-based digital teaching materials obtained a student response questionnaire percentage value of 88% with very good qualifications. The effectiveness of the media is reviewed from the results of students' pretests and postests with a medium N-gain value so that it can be concluded that android-based digital teaching materials are effective.